The Meteoritical Bulletin, No. 95 - Weisberg, M.; Smith, C.; Benedix, Gretchen; Folco, L.; Righter, K.; Zipfel, J.; Yamaguchi, A.; Aoudjehane, H.C. (John Wiley & Sons, Inc., 2009)
The Meteoritical Bulletin No. 95 reports 1093 (282 non-Antarctic and 801 Antarctic) newly approved meteorite names and their recovery histories, macroscopic descriptions, petrography, mineral compositions and geochemistry. Meteorites reported include lunar meteorites, eucrites, mesosiderites, angrites, ureilites, an acapulcoite, and H, L, LL, R, CO, CM, CK and CV chondrites. Three new falls, the Bunburra Rockhole (Australia) eucrite and the recent (Nov., 2008) Buzzard Coulee (Canada) H4 chondrite, and Tamdakht (Morocco) H5 chondrite are reported.